Geochemical impacts of oxygen impurities on subsurface biomethane storage - Zaid Jangda; Lorraine Boak; Robbie Skivington; Hunter Keil; Ali Daoud; Martin J. Maple; Andreas Busch (Gas Science and Engineering, 2026)

Comparative toxicity of plant protection products, their active substances and mixtures in zebrafish embryos and HepaRG cells - Bente Nissen; Alkiviadis Stagkos-Georgiadis; Martin Krauss; Denise Bloch; Wibke Busch (Archives of Toxicology, 2026)
The intensive use of plant protection products (PPPs) is essential in modern agriculture to ensure food security. PPPs are complex formulations of active substances (ASs) and co-formulants, yet regulatory risk assessment primarily focuses on AS toxicity, often overlooking combined effects. This study assessed the toxicity of three commercial PPPs, their AS-mixtures, and a co-formulant using the in vitro HepaRG liver cell assay and the in vivo zebrafish embryo toxicity test (ZFET). Product 1 contained the AS Benzovindiflupyr (Benzo), and Product 2 contained Benzo and Prothioconazole (Pro). Product 3 contained Pro and Tebuconazole (Teb) and the co-formulant N,N-Dimethyldecanamide (DDA), which was singled out for further investigation. AS were tested in different concentration ranges from 0.03 to 105 µmol/L in the ZFET and from 12.8 to 454.8 µmol/L in HepaRG cells. AS-mixtures were tested from 0.06 to 50 µmol AS/L (ZFET) and from 7.7 to 312.0 µmol AS/L (HepaRG). PPPs were tested from 0.02 to 29.8 µmol AS/L (ZFET) and from 2.9 to 312.0 µmol AS/L (HepaRG). PPPs were either more or as toxic as their respective AS-mixtures. In the ZFET, Products 1 and 2 showed similar toxicity to their AS-mixtures, while Product 3 showed a fourfold increase. In HepaRG cells, Product 1 was four times and Product 3 three times more toxic than their mixtures. Concentration addition models underestimated observed effects, particularly for Product 3, where co-formulants increased internal AS concentrations in zebrafish embryos. These findings underscore the need for whole mixture-based risk assessment for selected PPPs and support using integrated in vitro/in vivo approaches. Our study highlights the need for holistic PPP evaluation to improve safety assessments and regulatory strategies.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Proteinimport über die mitochondriale Innenmembran - Jakob D. Busch; Laura F. Fielden; Martin van der Laan; Nils Wiedemann (BIOspektrum, 2024)
The majority of mitochondrial proteins are nuclear-encoded and translated in the cytosol with an amino-terminal targeting signal called a presequence. Mitochondrial presequences are able to form amphiphilic α-helices with a positively charged and a hydrophobic side. The essential presequence translocase subunit Tim17 forms a cavity exposed to the bilayer, which harbors a negatively charged patch to initiate the translocation of positively charged presequences across the inner membrane.

Exploring an unknown: Representative sample survey on structure and energy-related quality of the non-residential building stock in Germany - Michael Hörner; Holger Cischinsky; Martin Behnisch; Roland Busch; Julian Bischof; Markus Rodenfels; André Hartmann; Robert Hecht; Gotthard Meinel; Martin Schorcht; Steffen Schwarz; Guido Spars; et al. (Building and Environment, 2024)

Role of pH-sensing receptors in colitis - Martin Hausmann; Klaus Seuwen; Cheryl de Vallière; Moana Busch; Pedro A. Ruiz; Gerhard Rogler (Pflügers Archiv - European Journal of Physiology, 2024)
Low pH in the gut is associated with severe inflammation, fibrosis, and colorectal cancer (CRC) and is a hallmark of active inflammatory bowel disease (IBD). Subsequently, pH-sensing mechanisms are of interest for the understanding of IBD pathophysiology. Tissue hypoxia and acidosis—two contributing factors to disease pathophysiology—are linked to IBD, and understanding their interplay is highly relevant for the development of new therapeutic options. One member of the proton-sensing G protein-coupled receptor (GPCR) family, GPR65 (T-cell death-associated gene 8, TDAG8), was identified as a susceptibility gene for IBD in a large genome-wide association study. In response to acidic extracellular pH, GPR65 induces an anti-inflammatory response, whereas the two other proton-sensing receptors, GPR4 and GPR68 (ovarian cancer G protein-coupled receptor 1, OGR1), mediate pro-inflammatory responses. Here, we review the current knowledge on the role of these proton-sensing receptors in IBD and IBD-associated fibrosis and cancer, as well as colitis-associated cancer (CAC). We also describe emerging small molecule modulators of these receptors as therapeutic opportunities for the treatment of IBD.

Skin optical properties from 200 to 300 nm support far UV-C skin-safety in vivo - Daniela F. Zamudio Díaz; Anna Lena Klein; Martin Guttmann; Paula Zwicker; Loris Busch; Marius Kröger; Holger Klose; Sascha Rohn; Johannes Schleusener; Martina C. Meinke (Journal of Photochemistry and Photobiology B: Biology, 2023)

Evaluation of DNA lesions and radicals generated by a 233 nm far-UVC LED in superficial ex vivo skin wounds - Loris Busch; Marius Kröger; Johannes Schleusener; Anna Lena Klein; Silke B. Lohan; Martin Guttmann; Cornelia M. Keck; Martina C. Meinke (Journal of Photochemistry and Photobiology B: Biology, 2023)

Assessment of angiogenesis-related parameters in juvenile idiopathic arthritis-associated uveitis - Karoline Baquet-Walscheid; Lena Wildschütz; Maren Kasper; Martin Busch; Solon Thanos; Dirk Bauer; Monika Stoll; Simone König; Arnd Heiligenhaus (Molecular Biology Reports, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Real Time Modelling of Burden Components Distribution During Hopper Outflow and Burdening Via a Rotating Chute - Stephan Hojda; Martin Pollet; Heike Busch; Rongshan Lin; Katharina Amend; Frank Rückert (BHM Berg- und Hüttenmännische Monatshefte, 2022)

Promoting FAIR Data Through Community-driven Agile Design: the Open Data Commons for Spinal Cord Injury (odc-sci.org) - Abel Torres-Espín; Carlos A. Almeida; Austin Chou; J. Russell Huie; Michael Chiu; Romana Vavrek; Jeff Sacramento; Michael B. Orr; John C. Gensel; Jeffery S. Grethe; Maryann E. Martone; Karim Fouad; et al. (Neuroinformatics, 2022)
The past decade has seen accelerating movement from data protectionism in publishing toward open data sharing to improve reproducibility and translation of biomedical research. Developing data sharing infrastructures to meet these new demands remains a challenge. One model for data sharing involves simply attaching data, irrespective of its type, to publisher websites or general use repositories. However, some argue this creates a ‘data dump’ that does not promote the goals of making data Findable, Accessible, Interoperable and Reusable (FAIR). Specialized data sharing communities offer an alternative model where data are curated by domain experts to make it both open and FAIR. We report on our experiences developing one such data-sharing ecosystem focusing on ‘long-tail’ preclinical data, the Open Data Commons for Spinal Cord Injury (odc-sci.org). ODC-SCI was developed with community-based agile design requirements directly pulled from a series of workshops with multiple stakeholders (researchers, consumers, non-profit funders, governmental agencies, journals, and industry members). ODC-SCI focuses on heterogeneous tabular data collected by preclinical researchers including bio-behaviour, histopathology findings and molecular endpoints. This has led to an example of a specialized neurocommons that is well-embraced by the community it aims to serve. In the present paper, we provide a review of the community-based design template and describe the adoption by the community including a high-level review of current data assets, publicly released datasets, and web analytics. Although odc-sci.org is in its late beta stage of development, it represents a successful example of a specialized data commons that may serve as a model for other fields.

Development of an AAV9-RNAi-mediated silencing strategy to abrogate TRPM4 expression in the adult heart - Rebekka Medert; Andreas Jungmann; Staffan Hildebrand; Martin Busch; Dirk Grimm; Veit Flockerzi; Oliver J. Müller; Patrick Most; Dagmar Schumacher; Marc Freichel (Pflügers Archiv - European Journal of Physiology, 2021)
The cation channel transient receptor potential melastatin 4 (TRPM4) is a calcium-activated non-selective cation channel and acts in cardiomyocytes as a negative modulator of the L-type Ca 2+ influx. Global deletion of TRPM4 in the mouse led to increased cardiac contractility under β-adrenergic stimulation. Consequently, cardiomyocyte-specific inactivation of the TRPM4 function appears to be a promising strategy to improve cardiac contractility in heart failure patients. The aim of this study was to develop a gene therapy approach in mice that specifically silences the expression of TRPM4 in cardiomyocytes. First, short hairpin RNA miR30 (shRNA miR30 ) sequences against the TRPM4 mRNA were screened in vitro using lentiviral transduction for a stable expression of the shRNA cassettes. Western blot analysis identified three efficient shRNA miR30 sequences out of six, which reduced the endogenous TRPM4 protein level by up to 90 ± 6%. Subsequently, the most efficient shRNA miR30 sequences were delivered into cardiomyocytes of adult mice using adeno-associated virus serotype 9 (AAV9)-mediated gene transfer. Initially, the AAV9 vector particles were administered via the lateral tail vein, which resulted in a downregulation of TRPM4 by 46 ± 2%. Next, various optimization steps were carried out to improve knockdown efficiency in vivo. First, the design of the expression cassette was streamlined for integration in a self-complementary AAV vector backbone for a faster expression. Compared to the application via the lateral tail vein, intravenous application via the retro-orbital sinus has the advantage that the vector solution reaches the heart directly and in a high concentration, and eventually a TRPM4 knockdown efficiency of 90 ± 7% in the heart was accomplished by this approach. By optimization of the shRNA miR30 constructs and expression cassette as well as the route of AAV9 vector application, a 90% reduction of TRPM4 expression was achieved in the adult mouse heart. In the future, AAV9-RNAi-mediated inactivation of TRPM4 could be a promising strategy to increase cardiac contractility in preclinical animal models of acute and chronic forms of cardiac contractile failure.

Population trends of common breeding birds in Germany 1990–2018 - Johannes Kamp; Claudia Frank; Sven Trautmann; Malte Busch; Rainer Dröschmeister; Martin Flade; Bettina Gerlach; Johanna Karthäuser; Friederike Kunz; Alexander Mitschke; Johannes Schwarz; Christoph Sudfeldt (Journal of Ornithology, 2021)
Biodiversity monitoring is important as it allows to prioritize research into the causes of declines and assessing the efficacy of conservation measures. Regional assessments are valuable, because conservation policies and management are often implemented on national and sub-national level. We analyzed data from the German Common Bird Monitoring for 1990–2018. We derived indices of population size using standard log-linear models, based on point counts and route territory mapping at up to 1200 plots annually. We summarized species trends by ecological trait groups. Among the 93 common breeding birds, farmland birds declined strongly, birds of settlements declined. Forest birds initially declined, but recovered after ca. 2010. Wetland birds increased strongly, albeit the number of species with data was low. Consistent declines were found in ground-nesting birds, granivorous and invertebrate (other than insect)-feeding birds. Trends of insectivorous birds were stable on average, but farmland insectivores declined strongly since the year 2000. Long-distance migrants showed more negative trends compared to short-distance migrants and resident species. Species with narrow habitat niche declined disproportionally. Trends over the entire period were more negative in common species in the dataset (with a German breeding population of > 50 K and < 1 M pairs). On the opposite, short-term trends were more negative in less common species (< 50 K pairs). Cold-adapted species showed largely negative, warm-adapted largely positive trends. Multi-species indicators showed no directional change (i.e., a change from decline to increase or vice versa) conditional on the inclusion or omission of single species, but the magnitude of change was affected in groups with low sample size. This suggests that efforts should be made to develop robust monitoring schemes for rarer species that are not covered by the analyses here. We conclude that conservation policies in Germany should aim at halting the worrying declines in ground-nesting, often insectivorous, farmland birds. The recovery of forest and wetland birds is encouraging, but future trends need to be monitored. Ongoing climate change will affect species directly (via their thermal niche) and indirectly (e.g., through more forest disturbance). Conservation strategies will, therefore, need to consider species adaptation to environmental and climate change, e.g., in better protected area connectivity and management.

Phenotypic Differences in Primary Murine Microglia Treated with NOD1, NOD2, and NOD1/2 Agonists - Susanne Wasmuth; Tida Viola Jalilvand; Björn Laffer; Martin Busch; Dirk Bauer; Thomas Langmann; Solon Thanos; Maren Kasper; Arnd Heiligenhaus (Journal of Molecular Neuroscience, 2020)

A comprehensive and comparative phenotypic analysis of the collaborative founder strains identifies new and known phenotypes - Heike Kollmus; Helmut Fuchs; Christoph Lengger; Hamed Haselimashhadi; Molly A. Bogue; Manuela A. Östereicher; Marion Horsch; Thure Adler; Juan Antonio Aguilar-Pimentel; Oana Veronica Amarie; Lore Becker; Johannes Beckers; et al. (Mammalian Genome, 2020)
The collaborative cross (CC) is a large panel of mouse-inbred lines derived from eight founder strains (NOD/ShiLtJ, NZO/HILtJ, A/J, C57BL/6J, 129S1/SvImJ, CAST/EiJ, PWK/PhJ, and WSB/EiJ). Here, we performed a comprehensive and comparative phenotyping screening to identify phenotypic differences and similarities between the eight founder strains. In total, more than 300 parameters including allergy, behavior, cardiovascular, clinical blood chemistry, dysmorphology, bone and cartilage, energy metabolism, eye and vision, immunology, lung function, neurology, nociception, and pathology were analyzed; in most traits from sixteen females and sixteen males. We identified over 270 parameters that were significantly different between strains. This study highlights the value of the founder and CC strains for phenotype-genotype associations of many genetic traits that are highly relevant to human diseases. All data described here are publicly available from the mouse phenome database for analyses and downloads.

Prospects and challenges of multi-omics data integration in toxicology - Sebastian Canzler; Jana Schor; Wibke Busch; Kristin Schubert; Ulrike E. Rolle-Kampczyk; Hervé Seitz; Hennicke Kamp; Martin von Bergen; Roland Buesen; Jörg Hackermüller (Archives of Toxicology, 2020)
Exposure of cells or organisms to chemicals can trigger a series of effects at the regulatory pathway level, which involve changes of levels, interactions, and feedback loops of biomolecules of different types. A single-omics technique, e.g., transcriptomics, will detect biomolecules of one type and thus can only capture changes in a small subset of the biological cascade. Therefore, although applying single-omics analyses can lead to the identification of biomarkers for certain exposures, they cannot provide a systemic understanding of toxicity pathways or adverse outcome pathways. Integration of multiple omics data sets promises a substantial improvement in detecting this pathway response to a toxicant, by an increase of information as such and especially by a systemic understanding. Here, we report the findings of a thorough evaluation of the prospects and challenges of multi-omics data integration in toxicological research. We review the availability of such data, discuss options for experimental design, evaluate methods for integration and analysis of multi-omics data, discuss best practices, and identify knowledge gaps. Re-analyzing published data, we demonstrate that multi-omics data integration can considerably improve the confidence in detecting a pathway response. Finally, we argue that more data need to be generated from studies with a multi-omics-focused design, to define which omics layers contribute most to the identification of a pathway response to a toxicant.

The accessory magnocellular neurosecretory system of the rostral human hypothalamus - Morten Møller; Johannes R. Busch; Christina Jacobsen; Sissel B. Lundemose; Niels Lynnerup; Martin F. Rath; Jytte Banner (Cell and Tissue Research, 2018)

Habitat preferences and breeding success of Whinchats (Saxicola rubetra) in the Westerwald mountain range - Klaus Fischer; Ralf Busch; Georg Fahl; Markus Kunz; Martin Knopf (Journal of Ornithology, 2013)

Innovations in phenotyping of mouse models in the German Mouse Clinic - Helmut Fuchs; Valérie Gailus-Durner; Susanne Neschen; Thure Adler; Luciana Caminha Afonso; Juan Antonio Aguilar-Pimentel; Lore Becker; Alexander Bohla; Julia Calzada-Wack; Christian Cohrs; Anna Dewert; Barbara Fridrich; et al. (Mammalian Genome, 2012)

microRNAs in the regulation of dendritic cell functions in inflammation and atherosclerosis - Martin Busch; Alma Zernecke (Journal of Molecular Medicine, 2012)

Comparative analysis of Neph gene expression in mouse and chicken development - Linus A. Völker; Marianne Petry; Mohammad Abdelsabour-Khalaf; Heiko Schweizer; Faisal Yusuf; Tilman Busch; Bernhard Schermer; Thomas Benzing; Beate Brand-Saberi; Oliver Kretz; Martin Höhne; Andreas Kispert (Histochemistry and Cell Biology, 2012)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

A molecular biological protocol to distinguish potentially human pathogenic Stenotrophomonas maltophilia from plant‐associated Stenotrophomonas rhizophila - Kathrin Ribbeck‐Busch; Anja Roder; Dirk Hasse; Wietse De Boer; José Luis Martínez; Martin Hagemann; Gabriele Berg (Environmental Microbiology, 2005)
Summary In recent years, the importance of the Gram‐negative bacterium Stenotrophomonas as an opportunistic pathogen as well as in biotechnology has increased. The aim of the present study was to develop new methods for distinguishing between strains closely related to the potentially human pathogenic Stenotrophomonas maltophilia and those closely related to the plant‐associated Stenotrophomonas rhizophila . To accomplish this, 58 strains were characterized by 16S rDNA sequencing and amplified ribosomal DNA restriction analysis (ARDRA), and the occurrence of specific functional genes. Based on 16S rDNA sequences, an ARDRA protocol was developed which allowed differentiation between strains of the S. maltophilia and the S. rhizophila group. As it was known that only salt‐treated cells of S. rhizophila were able to synthesize the compatible solute glucosylglycerol (GG), the ggpS gene responsible for GG synthesis was used for differentiation between both species and it was confirmed that it only occurred in S. rhizophila strains. As a further genetic marker the smeD gene, which is part of the genes coding for the multidrug efflux pump SmeDEF from S. maltophilia , was used. Based on the results we propose a combination of fingerprinting techniques using the 16S rDNA and the functional genes ggpS and smeD to distinguish both Stenotrophomonas species.

Pharmacokinetics of intravenous etoposide in patients with breast cancer: influence of dose escalation and cyclophosphamide and doxorubicin coadministration - Dagmar Busse; Gudrun Würthwein; Christiane Hinske; Georg Hempel; Martin Fromm; Michel Eichelbaum; Heyo Kroemer; Friedrich Busch (Naunyn-Schmiedeberg's Archives of Pharmacology, 2002)